BAURAN PEMASARAN BUNGA KRISAN PADA KELOMPOK TANI SAHABAT TANI DI KELURAHAN KAKASKASEN DUA KECAMATAN TOMOHON UTARA KOTA TOMOHON - Guntur Raharjo; Jenny Baroleh; Tommy F. Lolowang; Gene Kapantow (COCOS, 2014)
ABSTRACTGuntur Raharjo Marketing Mix of chrysanthemum flower on Sahabat Tani Group at Kakaskasen Dua Village, Tomohon Utara sub district, Tomohon City. Under guidance of Ir. J. Baroleh, Msi as a Chairman, , Dr. Ir. T. F. Lolowang, Msi., and Dr. Ir. G. Kapantow, Mikomp, MSc as members.The objectives of this research is to examine the marketing mix of chrysanthemum at Kakaskasen Dua Village, Tomohon Utara sub district, Tomohon City. And to examine the marketing margin of each institution involved in the Sahabat tani group.Data collection was conducted for three months, since May 2014 until July 2014. The data obtained are primary and secondary data. The primary data obtained through the survey directly to the farmer groups at Kakaskasen Dua Village, Tomohon Utara sub district, Tomohon City. Secondary data optained through agencies associated with this research. Sampling was done by purposive sampling technique that intentionally took ten farmers who are members of the Sahabat Tani Group. The analysis used in this study is descriptive analysis.The research results indicated that the marketing mix of Sahabat Tani Group, were product, price, place and promotion as well as marketing margin shown in every agency involved in Sahabat Tani Group.